Penerapan Web Api Untuk Sentralisasi Data Sistem Pembukuan - Dwiputra, Henrikus Karel; Wibowo, Argo; Proboyekti, Umi (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
Financial business is a business that focuses on the financial sector. One type of financial business is a provider of lending services in the form of money or goods. The Remedial Department is a department in a company engaged in the financial sector and has the task of marking, evaluating and recovering loans that have been issued by the company. In carrying out its duties the Remedial Department already has a system called Harbag, but this system is considered ineffective because it only contains HTML and does not have a database and architecture. So that the system can only do input and output only. Therefore, the Remedial Department has to input data several times. This research offers a solution in the form of creating an API that is useful for building systems to assist the work of the Remedial Department. This system is integrated with a web service that allows data to be centralized. Due to centralized data, the Remedial Department does not need to enter data repeatedly because data can be accessed between branches. This research was developed using the Personal Extreme Programing (PXP) method and utilizing PL/SQL in Oracle and SOA in SoftwareAG.